Quality Improvement Through Visualization of Software and Systems - Liggesmeyer, Peter; Barthel, Henning; Ebert, Achim; Heidrich, Jens; Keller, Patric; Yang, Yi; Wickenkamp, Axel (IntechOpen, 2012)
None